PENGARUH PENEGAKAN HUKUM TERHADAP PERKEMBANGAN TINDAK PIDANA NARKOTIKA DI KABUPATEN BENGKALIS - Riando, Ridho Gus; Artina, Dessy; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Article 54 of Law Number 35 of 2009 concerning Narcotics states that narcotics addicts are required to undergo medical and social rehabilitation. However, this did not happen, especially in the jurisdiction of Bengkalis Regency. The traffickers were sentenced to prison and put in the same place as the traffickers. This is also exacerbated by the increasing number of narcotics crimes from 2017 to 2020. The objectives of writing this thesis are; First, law enforcement on the development of narcotics in Bengkalis Regency, Second, the influence of law enforcement on the development of narcotics in Bengkalis Regency, Third, factors that become obstacles in law enforcement against narcotics development in Bengkalis Regency.This type of research can be classified in the type of sociological juridical research, this research was conducted at the Bengkalis Resort Police, the Bengkalis District Attorney, the Bengkalis District Court and the Bengkalis Correctional Institution, while the population and sample are all parties related to the problems studied in this study, the data sources used are primary data and secondary data, methods data collection in this study by interviews and literature study.From the results of the research problem, there are three main things that can be concluded, First, law enforcement carried out by the four sub-judicial systems is in the form of preventive and repressive law enforcement, Second, there is no influence from law enforcement that has been carried out by the four subï¿½judicial systems, This is caused by factors of the apparatus and the factors of the community itself, especially in the economic field, Third, the factors that become obstacles in law enforcement against the development of narcotics crime are the geographical condition of Bengkalis Regency, lack of personnel, facilities and facilities that are less supportive, limited funds and lack of public concern or participation. The author's suggestions, First, all relevant institutions in order to improve the quality and quantity of each institution, Second, to the local government of Bengkalis Regency to play a greater role in eradicating narcotics crime, providing special operational budgets related to narcotics eradication, building or providing places/rehabilitation homes for narcotics abusers and immediately formed the District-level National Narcotics Agency (BNNK).Keywords: Law Enforcement - Rehabilitation - Narcotics